Intercropping Pteris cretica and Spinacia oleracea L. with peanut enhances arsenic removal and soil remediation - Kama, Rakhwe; Nabi, Farhan; Aidara, Maimouna; Huang, Peiyi; Qadir, Muslim; Diatta, Sekouna; Ma, Chongjian; Li, Huashou (Frontiers in Plant Science, 2025)
Arsenic (As) exposure through agricultural soil contamination poses significant health risks and threatens food security. This study explored the efficacy of hyperaccumulator plant diversity and intercropping systems in enhancing As removal from contaminated soil while simultaneously reducing As uptake in peanuts (Arachis hypogaea L.). Thus, a pot experiment was conducted using As-contaminated soil, peanut plants, and hyperaccumulator species as the experimental materials. The experimental treatments included monocultured peanuts (Ck) and peanuts intercropped with Pteris cretica. (P*Pc), intercropped peanut with Spinacia oleracea L. (P*So), and intercropped peanut with P. cretica and S. oleracea L. (P*Pc*So). Our findings revealed that the intercropping system significantly reduced soil As levels compared to monocropping. In addition, peanut As uptake was significantly decreased in hyperaccumulator plants, with enhanced effects under hyperaccumulator plant diversity, minimizing the risk of As transfer to the food chain. Moreover, the As removal rate was higher under intercropping than under monocropping, with the highest removal rate of 88% under intercropped peanut/P. cretica/S. oleracea L., followed by peanut/S. oleracea L. (81%) and peanut/P. cretica (80%). The results demonstrate the potential of using diverse hyperaccumulator plants and intercropping systems as sustainable and effective methods for remediating As-contaminated soils, while simultaneously ensuring food safety. However, further research is needed to elucidate the underlying mechanisms driving these effects and to optimize the phytoremediation of As-contaminated soil and crop production.